Pengujian Struktur Beton Pada Jembatan II Di Sulawesi Tengah Dengan Metode Ultrasonic Pulse Velocity (UPV), Rebar Scanner dan Hammer Test - Sudarso; Fahmy (Universitas Veteran Bangun Nusantara, 2025)
The Borone bridge in Sulawesi is being tested for concrete strength using the ultrasonic pulse velocity (UPV) method. UPV is a concrete test using an ultrasonic wave method, which measures the travel time of the wave. This method measures travel time which is measured by measuring time and displayed in the form of wave speed. From the UPV test results of the Mangtangisi bridge, it was found that the quality of the concrete was low. The average speed value is 2,581m/s. The concrete compressive strength value is 21,64 MPa